Integrating mobile ad hoc network into mobile IPv6 network - Ali, Adel; Abdol Latiff, Liza; Fisal, Norsheila (Springer Berlin / Heidelberg, 2004)
In the future more and more devices connected to the Internet will be wireless. Wireless networks can be classified into two types of networks: network with infrastructure (i.e. networks with base stations, gateway and routing support), which is called Mobile IP, and network without infrastructure which is called ad hoc networks. Mobile IP tries to solve the problem of how a mobile node may roam from its network to foreign network and still maintain connectivity to the Internet. Ad hoc network tries to solve the problem if the infrastructure is not available or inconvenient for its use such as in rural environments. Integrating ad hoc into Mobile IP provide new feature for Mobile ad hoc network such as Internet connectivity, streamline communication with another network. This paper presents the development of a test bed for integrating Mobile Ad hoc NETwork (MANET) into Mobile IPv6.